EDUKASI KESEHATAN UNTUK MENINGKATKAN PENGETAHUAN DAN PENCEGAHAN TETANUS PADA LUKA DI RUANG MELATI BARAT RSUD dr. SOEHADI PRIJONEGORO SRAGEN - Vicky Oktaviana; Ayu Rizky Nabila; Ika Indah Lestari; Irma Mustika Sari; Kushariati Kushariati (CV. Denasya Smart Publisher, 2026)
Background: Tetanus is a serious infectious disease caused by the bacterium Clostridium tetani. Tetanus often causes symptoms of muscle spasms, especially in the jaw and neck area. Clostridium tetani bacteria are commonly found in soil, dust, human and animal feces that produce exotoxins. These bacteria can infect the body through improper wound care. Lack of public knowledge regarding tetanus prevention management can result in complications and even death. Providing health education is one effort that can be done to increase public knowledge in preventing tetanus in wounds. Objective: This health education activity aims to increase public understanding and knowledge in preventing tetanus, especially in patients at risk, namely patients with wounds. Method: Health education is carried out through interactive lecture methods, and distribution of information media in the form of leaflets. Evaluation is carried out using pre-test and post-test instruments to measure the level of knowledge of participants. Results: A significant increase was seen from the pre-test results of 40% correct answers to 80% correct answers after health education. Conclusion: Health education is effective in increasing public literacy regarding tetanus prevention. Ongoing support from the community health center is essential to ensure safe wound care practices in the home environment.